Farmers’ strategies and modes of operation in smallholder irrigation schemes in South Africa : a case study of Mamuhohi Irrigation Scheme in Limpopo Province - Geyser, Mariette (University of Pretoria, 2013)
Dissertation (MInstAgrar)--University of Pretoria, 2010.